Global systematic review of primary immunodeficiency registries. (2nd July 2020) - Abolhassani, Hassan; Azizi, Gholamreza; Sharifi, Laleh; Yazdani, Reza; Mohsenzadegan, Monireh; Delavari, Samaneh; Sohani, Mahsa; Shirmast, Paniz; Chavoshzadeh, Zahra; Mahdaviani, Seyed Alireza; Kalantari, Arash; Tavakol, Marzieh; et al.
ABSTRACT: Introduction: During the last 4 decades, registration of patients with primary immunodeficiencies (PID) has played an essential role in different aspects of these diseases worldwide including epidemiological indexes, policymaking, quality controls of care/life, facilitation of genetic studies and clinical trials as well as improving our understanding about the natural history of the disease and the immune system function. However, due to the limitation of sustainable resources supporting these registries, inconsistency in diagnostic criteria and lack of molecular diagnosis as well as difficulties in the documentation and designing any universal platform, the global perspective of these diseases remains unclear. Areas covered: Published and unpublished studies from January 1981 to June 2020 were systematically reviewed on PubMed, Web of Science and Scopus. Additionally, the reference list of all studies was hand-searched for additional studies. This effort identified a total of 104614 registered patients and suggests identification of at least 10590 additional PID patients, mainly from countries located in Asia and Africa. Molecular defects in genes known to cause PID were identified and reported in 13852 (13.2% of all registered) patients. Expert opinion: Although these data suggest some progress in the identification and documentation of PID patients worldwide, achieving the basic requirement for the global PID burden estimation and registration of undiagnosed patients will require more reinforcement of the progress, involving both improved diagnostic facilities and neonatal screening.